2003
DOI: 10.1590/s1517-83822003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors of Escherichia coli isolated from calves with diarrhea in Brazil

Abstract: Two hundred and five Escherichia coli strains isolated from calves with diarrhea from mid-western Brazil were screened for the presence of virulence factors associated with bovine colibacillosis. One hundred and two (49.8%) of the E. coli strains produced toxins: Shiga toxins 1 (9.7%) and 2 (6.3%), α-hemolysin (9.7%), enterohemolysin (6.8%), Cytotoxic Necrotizing Factors type 1 (0.5%), and type 2 (4.4%), enterotoxins LT-II (8.3%) and STa (3.9%). No strain produced enterotoxin LT-I. Fimbrial adhesins F5 and F17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
5
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 36 publications
(14 reference statements)
6
42
5
10
Order By: Relevance
“…Colibacillosis is common in Brazil, as some studies have reported (Leomil et al, 2003;Salvadori et al, 2003). Among the 173 E. coli isolates studied from northwestern of São Paulo State, 85 (49.1%) were found to be positive for at least one of the virulence factors examined, a result similar to that reported by Salvadori et al (2003).…”
Section: Discussionsupporting
confidence: 72%
“…Colibacillosis is common in Brazil, as some studies have reported (Leomil et al, 2003;Salvadori et al, 2003). Among the 173 E. coli isolates studied from northwestern of São Paulo State, 85 (49.1%) were found to be positive for at least one of the virulence factors examined, a result similar to that reported by Salvadori et al (2003).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the prevalence (50%) of EHEC pathotype is higher compared against 1 (7.1%) of the isolates which haboured cnf (1) only and was regarded as NTEC (De Rycke et al 1999;Landraud et al 2000, Salvadoris et al 2003, Shahrani et al 2014, and 6 (42.9%) which haboured stx only and were grouped as STEC (Aslani et al 2008, Shahrani et al 2014. This result suggested that EHEC strains may be the predominant diarrhoeagenic E. coli pathotype isolated from dogs with diarrhoea in Iran.…”
Section: 4% a A D ( A 1 ) T E T ( A ) T E T ( B ) D F R ( A 1 ) S mentioning
confidence: 56%
“…Diarrhoeagenic E. coli isolate may belong to the enteroinvasive E. coli (EIEC), enterohaemorrhagic E. coli (EHEC), enteropathogenic E. coli (EPEC), entroaggregative E. coli (EAEC), necrotoxic E. coli (NTEC), enterotoxigenic/shiga-like toxin producing E. coli (STEC) or diffusely adherent E. coli (DAEC) strain/ pathotypes, depending on the type of virulent factor(s) elaborated and the type of lesion produced (Bien et al 2011, De Rycke et al 1999, Puno-Sarmiento et al 2013, Salvadoris et al 2003. Nevertheless, canine diarrhoea may not primarily be caused by E. coli, although pathogenic strains of E. coli has been widely incriminated in cases of diarrhoea in humans and animals (Aslani et al 2008, Salvadoris et al 2003, Shahrani et al 2014. In many clinical conditions of dogs such as canine distemper, parvoviral enteritis, coronavirus infection, helminthosis, etc and a myriad of non-infectious and toxic conditions, the integrity of intestinal mucosa is altered resulting in enteritis and diarrhoea (Hammermueler et al 1995, Torkan et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations